A novel framework for social life cycle assessment to achieve sustainable cultural tourism destinations - Javdan, Mojtaba; Ghalehteimouri, Kamran Jafarpour; Ghasemi, Moslem; Riazi, Arezu (Turyzm/Tourism, 2023)
Tourism has a significant multiplier effect on other socioeconomic sectors, leading to improved infrastructure and public services. Its environmental impact, however, remains a subject of concern and there has been a growing emphasis on increasing the sustainability of tourism attractions. Despite the global importance of sustainability evaluation, there are just a few widely accepted methodologies for evaluating it. The life cycle concept is utilised to assess environmental, economic and social impacts and one critical life cycle tool is social life cycle assessment (S-LCA). Tourism-associated activities are ideally suited for the elaboration of data related to social sustainability due to tourism-specific service specifications. As a result, the main question is how can S-LCA help to ensure the long-term viability of cultural tourism destinations. This paper investigates the theoretical evolution of both S-LCA and cultural tourism in order to answer this question. A new framework S-LCA for sustainable cultural tourist destinations is developed and examined, as are potential application gaps. The hypothesized S-LCA conceptual framework S-LCA can thus play an effective role in accomplishing the principles and objectives of sustainable tourism destination management by bringing all stakeholders’ interests together.